2010
DOI: 10.1186/1742-4755-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Choices on contraceptive methods in post-abortion family planning clinic in the northeast Brazil

Abstract: BackgroundIn Brazil, a Ministry of Health report revealed women who underwent an abortion were predominantly in the use of contraceptive methods, but mentioned inconsistent or erroneously contraceptive use. Promoting the use of contraceptive methods to prevent unwanted pregnancies is one of the most effective strategies to reduce abortion rates and maternal morbidity and mortality. Therefore, providing post-abortion family planning services that include structured contraceptive counseling with free and easy ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
4
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 22 publications
(38 reference statements)
6
32
4
5
Order By: Relevance
“…Generally women who live in large urban centers have greater access to abortion methods, abortion clinics as well as to health services 14 . Most of the women in this study had no previous abortion and this also occurred in another study at the same service between 2008 and 2010 15 . This finding may reflect on the existence of sub-reports on previous abortion, due to restrictive laws about abortion in Brazil like in most countries in Latin America, which makes them less likely to report previous abortions 16 .…”
Section: Discussionsupporting
confidence: 71%
“…Generally women who live in large urban centers have greater access to abortion methods, abortion clinics as well as to health services 14 . Most of the women in this study had no previous abortion and this also occurred in another study at the same service between 2008 and 2010 15 . This finding may reflect on the existence of sub-reports on previous abortion, due to restrictive laws about abortion in Brazil like in most countries in Latin America, which makes them less likely to report previous abortions 16 .…”
Section: Discussionsupporting
confidence: 71%
“…Hence, just hearing about availability of the methods may not be adequate to translate into the behaviour. 8 This fact was reflected in this study as one -fourth of the respondents had never used any FP.…”
Section: Practices Of Contraception Pre-abortionmentioning
confidence: 87%
“…Study in Brazil in similar settings of post abortion care has also reported high level of knowledge regarding contraceptive services but low level of consistent use of the contraceptive measures. 8 Moreover, having onefifth of the women not using contraception, vast majority of them from the most accessible place of the country, reflects that there is more need to give complete education and adequate skills to start the use and continuation of available contraceptive services.…”
Section: Perceptions Regarding Contraceptionmentioning
confidence: 99%
“…In a cross-sectional study at a family-planning clinic in Brazil, 97.4% of women of low economic status accepted a contraceptive method after postabortion counseling [18]. The most frequently chosen method was injectable contraceptives, followed by oral contraceptives and condoms [18].…”
Section: Discussionmentioning
confidence: 99%